Efektifitas Pupuk Organik Dan NPK Terhadap Pertumbuhan Dan Hasil Tanaman Pakcoy (Brassica Rapa L) - Endang Dwi Purbajanti Purbajanti; D.E. Turnip; Sutarno (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2022)
This study aims to examine the effectiveness of doses of organic fertilizer and NPK on the growth and yield of pakcoy (Brassica rapaL.)The research design used isRandomized Block Design (RAK) with 6 treatments consisting of (P0) = control, namely 50% NPK, (P1) = addition of buffalo manure 150 g/plant (37.5 tons/ha), (P2) = addition of fertilizer buffalo cage 200 g/plant (50 tons/ha), (P3)= addition of buffalo manure 250 g/plant (62.5 tons/ha), (P4)= addition of buffalo manure 300 g/plant (75 tons/plant) ha), (P5) = addition of 350 g of buffalo manure/plant (87.5 tons/ha). Parameters observed at the growth stage were plant height, number of leaves and plant diameter. Parameters observed in plant production were wet weight, dry weight and leaf area. The data obtained were then statistically processed using analysis of variance (F test) to determine the effect of doses of organic fertilizer and NPK on the growth and yield of pakcoy plants, then continued with DMRT (Duncan's Multiple Range Test) at 5% level to determine differences between treatments. The results showed that the addition of buffalo manure increased the growth and yield of pakcoy vegetables. The addition of NPK fertilizer at 0.04 g/plant and buffalo manure 200g/plant equivalent to 50 tons/ha was the most effective combination of fertilization and resulted in the highest growth and yield of pakcoy vegetables. The results showed that the addition of buffalo manure increased the growth and yield of pakcoy vegetables. The addition of NPK fertilizer at 0.04 g/plant and buffalo manure 200g/plant equivalent to 50 tons/ha was the most effective combination of fertilization and resulted in the highest growth and yield of pakcoy vegetables. The results showed that the addition of buffalo manure increased the growth and yield of pakcoy vegetables. The addition of NPK fertilizer at 0.04 g/plant and buffalo manure 200g/plant equivalent to 50 tons/ha was the most effective combination of fertilization and resulted in the highest growth and yield of pakcoy vegetables.